2009
DOI: 10.3329/jsr.v1i2.1873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leaf Positions on Total Phenolics, Flavonoids and Proanthocyanidins Content and Antioxidant Activities in Lantana Camara (L)

Abstract: Changes in the level of phenolics, flavonoids and proanthocyanidins with leaf positions were studied in L. camara twigs. Leaves at different positions (from apex to base) in a twig represented gradient increase in the leaf age, apical being the youngest leaves. The study showed that the fresh weight, dry weight and area of the leaves increased rapidly from I until IV position in a twig. Levels of phenolics remained unchanged from I to V leaf position, while a sharp increase in the levels of proanthocyanidins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 23 publications
8
35
0
1
Order By: Relevance
“…5). Our results are in line with previous studies on other species reporting on the decrease in phenolic compounds levels with increasing age (Andreotti et al, 2006;Bhakta and Ganjewala, 2009;Mondolot et al, 2006). Compared to basal leaves harvested from 6 months old artichoke plants, top positioned ones showed 18-, 6-, 6-, and 8-fold increases in 1,5-dicaffeoyl quinic acid, chlorogenic acid, cynaraoside, and luteolin-7-O-acetyl-glucoside, respectively.…”
Section: Quantification Of Metabolites Among Artichoke Leaf Samplessupporting
confidence: 95%
“…5). Our results are in line with previous studies on other species reporting on the decrease in phenolic compounds levels with increasing age (Andreotti et al, 2006;Bhakta and Ganjewala, 2009;Mondolot et al, 2006). Compared to basal leaves harvested from 6 months old artichoke plants, top positioned ones showed 18-, 6-, 6-, and 8-fold increases in 1,5-dicaffeoyl quinic acid, chlorogenic acid, cynaraoside, and luteolin-7-O-acetyl-glucoside, respectively.…”
Section: Quantification Of Metabolites Among Artichoke Leaf Samplessupporting
confidence: 95%
“…Previously, Randrianalijaona et al (2005) has reported seasonal changes in the chemical composition of essential oils in more than seventy L. camara from different parts of the world. Very recently, Bhakta and Ganjewala (2009) reported the effects of leaf position on the level of secondary metabolites in L. camara. These studies have clearly suggested the geographical, developmental stage of the plant, and ontogeny influence the essential oil and or biochemical compositions in L. camara.…”
Section: Antibacterial Activities Of L Camara Leaves and Flowersmentioning
confidence: 99%
“…Previously, Randrianalijaona et al (2005) have reported the seasonal changes in the chemical composition of essential oils in more than seventy L. camara from different parts of the world. Very recently, we reported ontogenic variation in secondary metabolites such as phenolics, anthocyanins, and proanthocyanidins in L. camara (Bhakta and Ganjewala 2009). However, in L. camara very few studies have so far been focused on the influence of seasonal, genetic, ontogenic, and developmental factors of the chemical composition.…”
mentioning
confidence: 97%
“…The mixture was then filtered and mixed with small amount of amyl alcohol at room temperature [Ganjewala et al, 2009]. The mixture was kept for observation of the color resulted from the alcoholic layer.…”
Section: Test For Alkaloidsmentioning
confidence: 99%
“…The powdered root prepared from the leaves and flowers, locally called ''Yewef Kolo'' (Amharic), protects against fever and cold (Mesfin et al, 2009). Earlier phytochemical screening works on the leaf, flower and aerial parts of revealed the presence of terpenoids, alkaloids, steroids (Ganjewala et al, 2009;Singh et al, 1991;Singh 1990), Lantalonic acid, lantic acid, lupeol derivatives, camarinic acid, camaric acid, camarilic acid and related, commonly called wild sage or sleeper weed is the most widely spread species of the The root system is very strong with a main taproot and a mat of many shallow side roots It is one of the traditional medicinal plants used in Ethiopia and other part of the world for treatment of various diseases such as diarrhea, ) and stomachache (Nayak et The plant also showed antifungal (Tripathi and ., 2006), antiproliferative al, antimicrobial activities germicidal activities . The powdered root in milk and tea prepared from the leaves and flowers, locally called rotects against fever and cold .…”
Section: Introductionmentioning
confidence: 99%